Specific Leaf Area, Jumlah Trikomata dan Kandungan Kalium Daun Semai Kakao (Theobroma cacao L.) Pada Kandungan Air Tanah Berbeda - Prihastanti, Erma - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2011)
The existence of global warming caused the climate change such as the occurrence of long dry seasonsassociated with ENSO (El Nino Southern Oscillation). The climatologists predict these events will occur more oftenin the future. Cocoa plants require a relatively uniform distribution of rainfall in the year without a long dry season.The existence of drought stress can affect the rate of decline in the growth and development such as leaf expansionrate and decreased availability of nutrients in the root zone. This study aims to determine changes in specific leafarea (SLA), the number trichomes and K + content of leaves of cocoa seedlings at different soil water content. Thisstudy uses 36 cacao plants with 12-month-old were grown for two months on medium soil with soil water content of75%, 50% and 25%. Parameters observed are the SLA, the number trikomata and K+ content of leaves. The resultsshowed the age of 12 months of cocoa seedlings planted on different soil water content showed differences in SLA,trichomes and K+ content of leaves. The seedling grown optimum when planted on soil water content of 75%,whereas in 50% soil water content began to decline in growth with decreasing SLA and without leaves trichomes.The development and growth of seedlings declined sharply if planted in soil water content of 25%.